Quality Control for Solar Irradiance Data - Yang, Dazhi; Yagli, Gokhan Mert; Quan, Hao (2018 IEEE Innovative Smart Grid Technologies - Asia (ISGT Asia), 2018)
With the advent of sensing technology, high-resolution data have become ubiquitous among various smart grid applications. Whereas the data provide valuable empirical evidence, they are often, if not always, subject to significant measurement uncertainty. However, nor is there any standardized procedure to quality control (QC) these data. In this regard, this paper investigates the well-known dataset from the Baseline Solar Radiation Network (BSRN). BSRN archives (mostly) 1-min solar irradiance data from 60 stations around the world for over two decades. A six-step QC procedure is demonstrated using the BSRN data.